Compost barns in Brazilian Subtropical region (Part 2): classification through multivariate analysis (Research, Society and Development, 2020)
The objective was to classify the dairy farms that use Compost bedded pack barn (CB) in the Brazilian subtropical region, in terms of farm structure, building aspects, environmental and compost bedded pack characteristics, and reports the variability among them. Additionally, this research identifies structural and management factors that interfere in the compost bedded pack quality. Farms (n = 30) were visited (January-March 2017), located on Subtropical region of Brazil, where CB measurements, managements and herd observations were performed. The cluster analysis was performed with the kmeans methodology to define the groups, and through iterations, the optimal number of groups was determined according to the Silhouette method. Descriptive statistics were used for the different groups of farms. The clustering analysis, based on 12 variables, resulted in the formation of three groups: “Conventional and adapted CB” (n=18, with new and adapted barns, of different sizes, full time using, with adequate pack characteristics or not), “Large conventional CB” (n = 6, larger barns, more similar to American models, full time using) and, “CB of partial use” (n = 6, used in hottest hours of the day or rainy season, with better pack characteristics among groups, although do not have fans ventilation and the bedded pack is stirring only once a day). The CB systems are heterogeneous, and the barns are characterized by their distinct sizes or period of utilization. The group “CB of partial use” presented better bedded pack characteristics even with less intensive bedding management, and without fan ventilation in the barns.